A novel absolute displacement measurement technology based on wavenumber resolved low coherence interferometry. (December 2015) - Zhao, Keqiang; Xie, Fang; Ma, Sen; Wang, Yunzhi; Chen, Liang
Abstract: This paper proposed a novel absolute displacement measurement technology which is based on the wavenumber spectrum of low coherence interferometry. The signal from a Michelson interferometer, which is derived from a broadband light source, is dispersed by a bulk dispersing grating. The interferometric signal of each wavelength is detected by a linear array charge coupled device (CCD). By transforming the wavelength spectrum of the signal into wavenumber spectrum, absolute displacement can be measured precisely by measuring the wavenumber difference between two neighboring peaks of the wavenumber spectrum. Unlike the normal low coherence interferometric measurement systems (LCIMS) which have to scan the optical path difference (OPD) of the interferometer in order to demodulate the measurand, there is no need of scanning action during the measurement procedure, which not only simplifies the measurement system but also improves the measurement speed greatly. A fiber Bragg grating (FBG) is employed to produce a feedback signal which is used to stabilize the Michelson interferometer so as to obtain high measurement precision. A step height with the calibrated value of 50 μm that is configurated with two gauge blocks is measured by the system. The measurement resolution is 6.03 nm and the standard deviation of 10 times measurement results is 6.8 nm. Highlights: The system can perform absolute measurement. There is no need of scanning action in this low coherence interferometric system. The measurement range is not limited by the wavelength. The system is suitable for on-line measurement.